Revival of Traditional Cascade Tanks for Achieving Climate Resilience in Drylands of South India - Chinnasamy, Pennan; Srivastava, Aman (Frontiers in Water, 2021)
Traditional tanks in arid regions of India have been working to address water demands of the public for more than 2000 years. However, recent decade is witnessing growing domestic and agricultural water demand coupled with rising encroachment and ignorance towards tanks; consequently, intensifying water shortage issues. While climate change is impacting at alarming rates, local agencies have forgotten these tanks that have aided in sustainable water supply solutions for decades apart from municipal water supply. This research, for the first time, estimates water supply-demand for an arid region in South India (Madurai) and lists out the benefits if tanks were managed and desilted. Exploratory investigations for documenting seasonal domestic and agricultural unmet water demand were conducted followed by their validation through ground-truthing across the study period 2002-2019. Results indicated high unmet domestic water demand, estimating ~73% (maximum 365 thousand cubic meters (TCM)) for summer (March to May) and ~33% (maximum 149 TCM) for winter (January and February), and high unmet agricultural water demand estimating ~90% (maximum 5,424 TCM) during North-East monsoon (October to December) and ~95% (maximum 5,161 TCM) during South-West monsoon (June to September). Erratic rainfall pattern was identified as a major cause for higher fluctuations in water availability inside tanks ranging 0%-50%, while lack of ownership resulted in increased siltation load ranging 30%-70% of the tank’s volume. The study found that the major portion of the unmet water demand can be accounted for through rehabilitation of the tanks, as under the rehabilitated tank irrigation scenario the tank storage could attain 200%-400% more water than the estimated agricultural water demand. It was concluded that if the cascade tanks were managed appropriately, they could have positive impacts by reducing floods and providing water for drought seasons.